A contribuição de modelos utilizando uma abordagem modelo - código - Jesus, Evaldo Dias de [UNESP] (2011)
In a world that is increasingly working with software, the need arises for effective approaches that encourage software reuse. The reuse practice must be aligned to a set of practices, procedures and methodologies that create a stable and high quality product. These questions produce new styles and approaches in the software engineering. In this way, this thesis aims to address concepts related to development and model-driven architecture. The model-driven approach provides significant aspects of the automated development, which helps it with produced models built in the specification phase. The definition of terms such as model, architecture and platform makes the focus becomes clearer, because for MDA and MDD is important to split between technical and business issues. Important processes are covered, so you can highlight the artifacts that are built into each stage of model-driven development. The stages of development: CSM, PIM, PSM and ISM, detailing the purpose of each phase in oriented models, making the end of each stage are gradually produced artifacts that may be specialized. The models are handled by different prospects for modeling, abstracting the concepts and building a set of details that portrays a specific scenario. This retraction can be a graphical or textual representation, however, in most cases is chosen a language modeling, for example, UML. In order to provide a practical view, this dissertation shows some tools that improve the construction of models and the code generate that assists in the development, keeping the documentation systemic. Finally, the paper presents a case study that refers to the theoretical aspects discussed throughout the dissertation, therefore it is expected that the architecture and the model-driven development may be able to explain important features to consider in software engineering